A Field Experiment on Moral Suasion and Tax Compliance Focusing on Under-Declaration and Over-Deduction - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2012)
Field experiments in the area of tax compliance are rare. This field experiment generates a unique data set with respect to individuals' under-declaration of income and wealth and over-deductions of tax credits by obtaining exclusive full access to the audits. Using this commune level data from Switzerland, the paper explores the influence of moral suasion on tax compliance. Moral suasion was introduced through a treatment in which taxpayers received a letter signed by the commune's fiscal commissioner containing normative appeals. Interestingly, I observe differences between under-declaration and over-deductions. Moreover, the overall finding is in line with former results that moral suasion has hardly any effect on taxpayers' compliance.
Keywords: H26; H71; 330; tax compliance; moral suasion; field experiment